ANALISIS EFISIENSI PEMASARAN DAN TRANSMISI HARGA CABAI RAWIT DI KECAMATAN WAKORUMBA UTARA KABUPATEN BUTON UTARA - Sri Yulistika; Rosmawaty Rosmawaty; Yusran Yusran (Universitas Halu Oleo, 2022)
This study aims to identify marketing channel patterns, analyze marketing margins, marketing efficiency and price transmission of cayenne pepper. To determine the sample of cayenne pepper farmers in the study using the Simple Random Sampling method and determining marketing institutions using Snowbal Sampling. The results showed that there are 2 marketing channels of cayenne pepper in North Wakorumba District, North Buton Regency, namely marketing channel I consisting of farmers - collectors - wholesalers - retailers and then marketed to final consumers, while marketing channel II starts from farmers - traders wholesaler-retailer which is then marketed to the final consumer. The total cost of the entire marketing channel I involved is Rp. 6,133.28/Kg, while in the marketing channel II is Rp. 3,577.8/Kg, the total marketing margin in the marketing channel I is Rp. 15,000/Kg, in the marketing channel II the total margin is IDR 10,000/Kg. The farmer share in marketing channel I is 75%, marketing channel II is 85% and the elasticity of price transmission in marketing channel I is 0.15 and for the elasticity of marketing channel II is 0.28. Both marketing institutions have elasticity < 1 or inelastic.